2020
DOI: 10.46743/2160-3715/2020.4180
|View full text |Cite
|
Sign up to set email alerts
|

Access to Eye Care Before and After Vision Loss: A Qualitative Study Investigating Eye Care Among Persons Who Have Become Blind

Abstract: Navigating access to eye care requires that patients recognize the need for screening and care, employ limited financial and social resources, manage complex health insurance policies, and access specialty clinical care. We investigated the experience of patients through the progression of vision loss to blindness, utilizing qualitative methods. We conducted structured telephone interviews with 28 persons with blindness throughout Oregon. Utilizing closed and open-ended questions, we explored patient experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Using a constant comparative approach they found that social support structures and personal readiness to change were important factors for some people, alongside familiar themes of geographic access and low trust in providers. 40 Elam and Lee conducted content analysis on data from four focus groups with American community members at risk of not attending eye services. Issues around health insurance, racism, unfriendly service at the clinic, and procrastination supplemented familiar themes of cost, trust, and fear.…”
Section: Introductionmentioning
confidence: 99%
“…Using a constant comparative approach they found that social support structures and personal readiness to change were important factors for some people, alongside familiar themes of geographic access and low trust in providers. 40 Elam and Lee conducted content analysis on data from four focus groups with American community members at risk of not attending eye services. Issues around health insurance, racism, unfriendly service at the clinic, and procrastination supplemented familiar themes of cost, trust, and fear.…”
Section: Introductionmentioning
confidence: 99%
“…SDOH are not negative or positive, and they affect society, whereas social risk factors (SRFs) explain how SDOH affect individuals. SRFs can be unfavorable social conditions associated with poor health and include high area deprivation, low income, lower education levels, and less access to health care . Understanding the SRFs driving health inequities creates the impetus for policy change.…”
Section: Introductionmentioning
confidence: 99%
“…SRFs can be unfavorable social conditions associated with poor health 3 and include high area deprivation, 4 low income, 5,6 lower education levels, [5][6][7] and less access to health care. 5,8 Understanding the SRFs driving health inequities creates the impetus for policy change.…”
mentioning
confidence: 99%